Using primary site as a predictor of survival in mantle cell lymphoma. Issue 8 (22nd January 2013) - Ambinder, Alexander J.; Shenoy, Pareen J.; Nastoupil, Loretta J.; Flowers, Christopher R.
Abstract: BACKGROUND: Mantle cell lymphoma (MCL) is a rare B cell lymphoma that varies in clinical behavior with some patients experiencing aggressive disease with short survival, whereas others have indolent behavior. We examined the association between primary disease site and survival in MCL patients to identify subgroups with distinct characteristics. METHODS: We analyzed the United States Surveillance, Epidemiology and End Results Program database for MCL cases reported from 2000 through 2009. Kaplan‐Meier curves and Cox proportional hazard models were used to estimate the effect of primary site on survival. RESULTS: Among 4477 cases included in our study, 19.6% of patients presented with an extranodal primary site. The most common extranodal primary sites were of the gastrointestinal (GI) tract (7.8%), the head and neck (6.2%), and the hematologic/reticuloendothelial systems (3.6%). Asians/Pacific Islanders were more likely than whites or blacks to have GI tract or head and neck disease ( P < .0001 and P = .002, respectively). Advanced disease and B symptoms were less common in those with primary disease of the GI tract or head and neck than in those with primary disease of the lymph nodes (both P < .0001). In a multivariate Cox regression model, patients with primary disease of the GI tract and head and neck had superior survival compared to those with primary disease of the lymph nodes; hazard ratios 0.75 (95% CI = 0.62‐0.90) and 0.68 (95% CI = 0.55‐0.85), respectively. CONCLUSIONS: Primary site of disease may be an important prognostic factor for patients with MCL. Further studies elucidating a biological basis for these differences are needed. Cancer 2013. © 2013 American Cancer Society. Abstract : In an analysis of patients with mantle cell lymphoma in the Surveillance, Epidemiology and End Results (SEER) database, patients with primary disease of the gastrointestinal tract and of the head and neck had improved survival compared to those with primary disease of the lymph nodes. Primary site of disease may be associated with favorable treatment strategies or tumor biology in patients with mantle cell lymphoma.